Exploring the clinical efficacy of different nonsurgical rehabilitation interventions for humeral lateral epicondylitis: A protocol for network meta-analysis. Issue 34 (26th August 2022) - Wan, Qing; Lan, Qin; Zhi, Fang; Lin, Xingzhen
Abstract : Background: Lateral epicondylitis is a common musculoskeletal disorder characterized by the decreased grip and upper limb strength and pain in the lateral aspect of the elbow joint. At present, shock wave, corticosteroid injection, platelet-rich plasma injection, and Dextrose prolotherapy therapy nonsurgical rehabilitation treatment methods are commonly used in clinical. However, the conclusions of studies comparing treatment efficacy between them are controversial, with most studies focusing on limited comparisons and a lack of direct and indirect comparisons between them, making it difficult to have a clearer and more comprehensive understanding of the efficacy between them. Purpose: To comprehensively compare the effectiveness of shockwave, corticosteroid injection, platelet-rich plasma injection, and Dextrose prolotherapy therapy for the treatment of external humeral lateral epicondylitis using a reticulo-meta-analysis. Methods: Randomized controlled trials on the effectiveness of shock wave, corticosteroid injection, platelet-rich plasma injection, and Dextrose prolotherapy therapy for the treatment of external humeral lateral epicondylitis were searched in PubMed, The Cochrane Library, CNKI, and Wan-Fang databases for the period January 1, 2016 to January 1, 2021 for each database. Two investigators independently screened the literature, extracted data according to inclusion and exclusion criteria, and evaluated the quality of the literature in parallel. Statistical analyses were performed using Stata 14.0 software to compare differences in efficacy between treatment measures using ratio and 95% confidence interval as effect indicators and to rank efficacy. Results: Nine randomized controlled trials with a total of 289 patients with external humeral lateral epicondylitis were included, involving 4 nonsurgical rehabilitation measures and 6 intervention options. Quadrilateral ring to test the inconsistency of each closed-loop study finding, and the results show that the inconsistency factor was bounded at 1.65, with lower 95% confidence interval of 0.47 and 2.84 for both, which in summary indicates that the formation between the treatment measures in this study indicates that each closed-loop inconsistency was good. The SUCRA curve showed that platelet-rich plasma injection + shockwave was the first treatment with an area under the curve of 86.9%. Six treatment measures were ranked as follows: platelet-rich plasma injection + shockwave > platelet-rich plasma injection > shockwave > corticosteroid > corticosteroid + shockwave > prolotherapy. Conclusions: It is believed that in the course of clinical practice, platelet-rich plasma injection combined with shockwave therapy can be preferred for patients with humeral epicondylitis.